Risk Factors for Short Stature in Children Born Small for Gestational Age at Full-Term - Ling, Lan; Chen, Ting; Zhang, Xin-Hua; Pan, Min-Hong; Gong, Hai-Hong; Zhang, Li-Na; Zhao, Meng; Chen, Xiao-Qing; Cui, Shu-Dong; Lu, Chao (Frontiers in Pediatrics, 2022)
Objective This study aims to identify the risk factors associated with short stature in children born small for gestational age (SGA) at full-term. Methods This was a retrospective study. The subjects were full-term SGA infants who were followed up until the age of 2 years. The risk factors for short stature were identified with univariate and multivariate analyses. Results Of 456 full-term SGA children enrolled in this study, 28 cases had short stature at 2 years of age. A significant decrease in placental perfusion was found in the short children group with intravoxel incoherent motion (IVIM) technology, which was an advanced bi-exponential diffusion-weighted imaging (DWI) model of magnetic resonance imaging (MRI) (p = 0.012). Compared to non-short children born SGA at full-term, the short children group underwent an incomplete catch-up growth. Mothers who suffered from systemic lupus erythematosus were more likely to have a short child born SGA (p = 0.023). The morbidity of giant placental chorioangioma was higher in the short children group. The pulsatility index (PI), resistivity index (RI), and systolic-diastolic (S/D) ratio of umbilical artery were higher in the short children group than in the non-short control group (p = 0.042, 0.041, and 0.043). Multivariate analysis demonstrated that decrease of perfusion fraction (fp) in IVIM of placental MRI, chromosomal abnormalities, short parental height, and absence of catch-up growth were associated with a higher risk of short stature in children born SGA at full-term. Conclusion Risk factors for short stature in full-term SGA children at 2 years of age included a decrease of perfusion fraction fp in IVIM of placental MRI, chromosomal abnormalities, and short parental height.